Berbagai Faktor yang Berpengaruh Terhadap Kualitas Hidup Penyelam Tradisional Penderita Penyakit Dekompresi - Sri Rahayu Widyastuti; Suharyo Hadisaputro; Munasik Munasik (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
Background: Decompression sickness is thought to have an effect on health-related quality of life (HRQL), however, not yet known factors that affect the quality of life on traditional divers with decompression sickness.Methods: This research was a mix methods research with case-control study design which strengthened by FGD. The participants were 66 volunteers, consist of  33 cases dan 33 controls. The data obtained from the study were analyzed using bivariate and multivariate analysis.Results: Variables that had been proven to affect poor quality of life were history of hypertension  comorbid (p = 0.010; OR = 65.476; 95% CI = 2.735 – 1,568), diving depth ≥ 30 meters (p = 0.014; OR = 38.410; 95% CI = 2.114 – 698.028), history of loss of consciousness during diving (p = 0.009; OR = 12.456, 95% CI = 1.884 – 82.363), diving duration ≥ 2 hours (p = 0.021; OR = 9.860; 95% CI = 1.410 – 68.943), suffering from anemia (p = 0.024; OR = 8.837; 95% CI = 1.332 – 58.632), frequency of decompression sickness history > 1 time (p = 0.020; OR = 8.834; 95% CI = 1.404 – 55.584).Conclusion: Factors that had been proven to affect poor quality of life on traditional diver with decompression sickness were the history of hypertension comorbid, diving depth ≥ 30 meters, history of loss of consciousness during diving, diving duration ≥ 2 hours, suffering from anemia, the frequency of previous decompression sickness > 1 time.